Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

A clothing store sells a customer 5 T-shirts and 3 pairs of shorts for [tex]\$66[/tex]. Another customer buys 15 T-shirts and 2 pairs of shorts for [tex]\$114[/tex]. How much is one T-shirt [tex](t)[/tex] and one pair of shorts [tex](s)[/tex]?

A. [tex]t = \[tex]$6, s = \$[/tex]12[/tex]
B. [tex]t = \[tex]$15, s = \$[/tex]2[/tex]
C. [tex]t = \[tex]$5, s = \$[/tex]3[/tex]
D. [tex]t = \[tex]$12, s = \$[/tex]6[/tex]


Sagot :

To determine the cost of one T-shirt [tex]\(t\)[/tex] and one pair of shorts [tex]\(s\)[/tex], we will set up and solve a system of linear equations based on the given information.

Let's denote:
- [tex]\(t\)[/tex] as the cost of one T-shirt.
- [tex]\(s\)[/tex] as the cost of one pair of shorts.

We have two customers and the following information:
1. The first customer buys 5 T-shirts and 3 pairs of shorts for a total of \[tex]$66. 2. The second customer buys 15 T-shirts and 2 pairs of shorts for a total of \$[/tex]114.

We can translate this information into two equations:
[tex]\[ 5t + 3s = 66 \tag{1} \][/tex]
[tex]\[ 15t + 2s = 114 \tag{2} \][/tex]

We will solve this system of equations step-by-step.

### Step 1: Solve one equation for one variable in terms of the other
First, we solve equation (1) for [tex]\(s\)[/tex]:
[tex]\[ 5t + 3s = 66 \][/tex]
Isolate [tex]\(s\)[/tex] by subtracting [tex]\(5t\)[/tex] from both sides:
[tex]\[ 3s = 66 - 5t \][/tex]
Divide by 3:
[tex]\[ s = 22 - \frac{5}{3}t \tag{3} \][/tex]

### Step 2: Substitute the expression from equation (3) into equation (2)
Substitute [tex]\(s = 22 - \frac{5}{3}t\)[/tex] into the second equation [tex]\(15t + 2s = 114\)[/tex]:
[tex]\[ 15t + 2\left(22 - \frac{5}{3}t\right) = 114 \][/tex]
Distribute 2 in the equation:
[tex]\[ 15t + 44 - \frac{10}{3}t = 114 \][/tex]
To combine like terms, convert [tex]\(15t\)[/tex] to a common denominator of 3:
[tex]\[ \frac{45}{3}t + 44 - \frac{10}{3}t = 114 \][/tex]
Combine the [tex]\(t\)[/tex] terms:
[tex]\[ \frac{35}{3}t + 44 = 114 \][/tex]
Subtract 44 from both sides:
[tex]\[ \frac{35}{3}t = 70 \][/tex]
Multiply both sides by 3 to clear the fraction:
[tex]\[ 35t = 210 \][/tex]
Divide by 35:
[tex]\[ t = 6 \][/tex]

### Step 3: Substitute [tex]\(t = 6\)[/tex] back into equation (3) to find [tex]\(s\)[/tex]
Using [tex]\(t = 6\)[/tex] in equation (3):
[tex]\[ s = 22 - \frac{5}{3}(6) \][/tex]
Calculate:
[tex]\[ s = 22 - 10 \][/tex]
[tex]\[ s = 12 \][/tex]

Therefore, the cost of one T-shirt ([tex]\(t\)[/tex]) is \[tex]$6, and the cost of one pair of shorts (\(s\)) is \$[/tex]12.

So, the correct answer is:
A. [tex]\(t = \$6, s = \$12\)[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.